Structural features of Fe-Al-vacancy system - Rokhmanov, N.Ya.; Onishchenko, V.V.; Laptev, I.N.; Parkhomenko, A.A. (Functional Materials, 2006)
The influence of structural defects on phase transformation in Fe-Al-vacancies system is considered. It has been shown that, due to existing trend to accumulation of point defects at increasing aluminum content in Fe-Al system alloys, the appearance of ferrite precipitates in Fe₃Al compound becomes thermodynamically favorable in the temperature region of the equilibrium α₁(Fe₃Al)-phase existence. Розглянуто вплив дефектiв структури на перебiг фазових перетворень у системi Fe-Al-вакансil. Показано, що внаслiдок iснуючої тенденцiї накопичення дефектiв структури зi збiльшенням вмiсту алюмiнiю у сплавах системи Fe-Al в iнтерметалiдi Fe₃Al в областi температур iснування рiвноважноl α₁(Fe₃Al)-фази термодинамiчно вигiдним стає поява видiлень фериту. Рассмотрено влияние дефектов структуры на протекание фазовых превращений в системе Fe-Al-вакансии. Показано, что вследствие существующей тенденции накопления дефектов структуры по мере увеличения содержания алюминия в сплавах системы Fe-Al, в интерметаллиде Fe₃Al в области температур существования равновесной α₁(Fe₃Al)-фазы термодинамически выгодным становится появление выделений феррита.